2018
DOI: 10.1016/j.abb.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin formulated in solid lipid nanoparticles has enhanced efficacy in Hodgkin's lymphoma in mice

Abstract: Curcumin reduces Hodgkin's lymphoma (HL) cell growth in vitro, but its unfavorable pharmacokinetics highlight the need for novel in vivo delivery systems. Thus, we explored whether formulation of curcumin in solid lipid nanoparticles (SLN-curc) or d-α-Tocopheryl polyethylene glycol 1000 succinate (TPGS) nanoparticles (TPGS-curc) could enhance its efficacy in mice. Curcumin formulated in SLN and in TPGS resulted in higher curcumin plasma levels in mice. Compared to vehicle-treated controls, SLN-curc and TPGS-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…To enhance targeting capability and solid-tumor penetration, Legumain-targeting strategy encapsulating HC were used by adding Legumain-targeted RR-11a into the liposomal nanoparticles (178, 179). In another study, the suitability of introducing Curcumin in solid lipid nanoparticles (SLN-curc) or d-α-Tocopheryl polyethylene glycol 1,000 succinate (TPGS) nanoparticles (TPGS-curc) was investigated in Hodgkin's lymphoma in mice, which SLN-curc was more superior compared to TPGS-curc in term of pharmacokinetic profile (180).…”
Section: Other Strategies In Targeting Stat3/5mentioning
confidence: 99%
“…To enhance targeting capability and solid-tumor penetration, Legumain-targeting strategy encapsulating HC were used by adding Legumain-targeted RR-11a into the liposomal nanoparticles (178, 179). In another study, the suitability of introducing Curcumin in solid lipid nanoparticles (SLN-curc) or d-α-Tocopheryl polyethylene glycol 1,000 succinate (TPGS) nanoparticles (TPGS-curc) was investigated in Hodgkin's lymphoma in mice, which SLN-curc was more superior compared to TPGS-curc in term of pharmacokinetic profile (180).…”
Section: Other Strategies In Targeting Stat3/5mentioning
confidence: 99%
“…Substantial evidence revealed that curcumin (4 mg/kg every 2 days for a total of 7 injections) exhibits a better treatment efficacy of doxorubicin (0.4 mg/kg) in cancer due to its efflux inhibitory effect of curcumin [92,93,94]. A study conducted by Guorgui et al [95] has shown that combination of curcumin (5 µM) and doxorubicin (0.4 mg/mL) demonstrated a stronger additive effect by reducing the proliferation of Hodgkin lymphoma (L-540) cells by 79%. The pharmacokinetic study also revealed that curcumin (5 mg/kg) could enhance the absorption of doxorubicin (5 mg/kg) and decrease drug efflux in vivo, suggesting that curcumin downregulates the intracellular levels of ATP-binding cassette (ABC) drug transporters [96].…”
Section: The Synergistic Effect Of Curcumin Combination Chemotherapymentioning
confidence: 99%
“…The data revealed that TPGS-curc (10 mg/kg body weight) shows a better in vivo kinetic profile than curcumin alone, suggesting that TPGS an ideal formulation to improve curcumin bioavailability in vivo. In addition, formulating curcumin in solid lipid nanoparticles (SLN-curc) (100 mg/kg of curcumin, 5 days per week for 18 days) exhibited a strong anticancer activity compared to curcumin alone (100 mg/kg, 5 days per week for 18 days) [95]. The data showed that SLN-curc increased cell cycle regulator (p21) and diminished the anti-apoptotic (XIAP and Mcl-1) levels [95].…”
Section: Nanoformulation Of Curcumin Combination Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugation of curcumin with SLN is another report for passive targeting of tumor tissues used in breast cancer with remarkably higher tissue availability [57]. In a similar study, growth inhibition of Hodgkin's lymphoma xenograft was observed by 50.5% in the case of curcumin-SLN receiving group [58]. For passive targeting of glioblastoma and melanoma, temozolomide-SLN showed higher inhibition in proliferation of these types of cancer tissues and lower cytotoxicity in healthy cells compared to temozolomide without SLN [59].…”
Section: Passive Targetingmentioning
confidence: 88%